(3SQGL GdeUdjs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GYde CSYOc Gddg JYGdi aj GdOGQjf PcQ aj GdaOGhi GdcHQi hGdaJGhi GdfGUQj hGdaJGhi GdTgGHj hUdGI GdeSYhOj ef de jYde aQGFV GdhVhA hZSd CYVGA GdKdGK s
(3BNQgG (B:s
(3GdaUd GdKGef aj HjGf eaSOGJ GdUdGI hgj GKfGf hCQHYhf GdChd GdJcde hgj HcdGe GdfGS YeOG Gh fGSjG aj Gdfhe haj GdjbXI bdjdG Ch cKjQG LgQG Ch NaGA hGdCcd hGdTQH hGdMOK YeOG JeJs
(3JHUQI GdeDda (B:s
(3fSHI GdOcJhQ ELSGf YHGS aj TPGQJ ef cJH eabhOg def jSei (B( (3GdQMHj (B) (3hgh ZjQ GdSjefGfj GdPj J (B499 (3g` MjK Cf eDda GdSQL jfbd Yef YGT aj GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\984s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3Gdabg GdYGes